Pengaruh Ketidakpastian Kerja Dan Beban Kerja Terhadap Motivasi Kerja Pegawai Suku Dinas Perpustakaan Kearsipan Jakarta Barat: The Effect of Job Uncertainty and Workload on the Work Motivation of Employees of the West Jakarta Archives Library Service - Gina Hoerun Nisa; Darkiman Ruminta; Dudi Duta Akbar (CV Warnak Johanna Nusantara, 2026)
Abstracts - The transformation of public service systems in the digital era, which demands greater efficiency, effectiveness, and service quality, has driven the West Jakarta Sub-Department of Library and Archives as a strategic institution in building a literacy-based society to face the challenges of job uncertainty and high workload that impact employee motivation. This study employs a quantitative approach with a causal associative design to examine the effect of job uncertainty and workload on employee motivation at the West Jakarta Sub-Department of Library and Archives. Using purposive sampling, 35 respondents were selected as the sample. Data were collected through questionnaires and interviews, then analyzed using multiple linear regression with validity, reliability, classical assumption, t-test, F-test, and coefficient of determination analyses assisted by SPSS version 26. The results indicate that job uncertainty and workload have a significant effect, both partially and simultaneously, on employee motivation, with t-values of 5.373 and 4.526, an F-value of 214.600, significance level < 0.001, and an R Square value of 0.931, showing that 93.1% of the variation in employee motivation is explained by these two variables. Keywords: Job Insecurity, Workload, Work Motivation